SAT0243 SUBPHENOTYPES IN POLYARTERITIS NODOSA (PAN): TARGET ORGAN ASSOCIATIONS OF A WORLDWIDE COLLABORATION STUDY. (2nd June 2020) - Karadag, O.; Bolek, E. C.; Furuta, S.; Emmi, G.; Hocevar, A.; Hinojosa-Azaola, A.; Mohammad, A. J.; Ugurlu, S.; Alibaz-Oner, F.; Yazici, A.; Quartuccio, L.; Bozzolo, E.; et al.
Abstract : Background: There is a paucity of information on the current phenotypes, ethnic and geographic differences of PAN. A global PAN study group has been working for clinical subphenotype and GWAS studies. Objectives: This study is aimed to look for target organ associations in PAN. Methods: PAN patients fulfilling the EMA vasculitis classification algorithm were recruited. In addition to baseline characteristics, treatment and outcome data, occurrence of any of the clinical manifestations related to PAN during disease course was recorded. Factor analysis was used to analyse target organ associations of 306 patients. Five factors were identified by factor analysis of variables sex, paediatric-onset, HBV, monogenic disease relationship, cutaneous features, musculoskeletal symptoms, constitutional symptoms and involved areas (abdominal, renal, neurologic, ENT, cardiac, pulmonary). Results: PAN cohort from 7 countries were used (Italy: n=59, Japan: n=39, Mexico: n=29, Slovenia: n=14, Sweden:11, TUR: n=106, UK: n=48). 306 (M/F: 171/135 and Caucasian 77.1%, Asian 13.4%, and Hispanic 9.5%) patients were included. 8 were HBV-related, and 22 of TUR patients had a monogenic form of disease (FMF n=15, DADA2 n=7). 21.8% of patients were cutaneous-only PAN patients. 48.4% of patients had radiologic, 64% had biopsy-proven PAN. Median age at disease onset was 40 (IQR 27.0-57.5) years. During a median 57 (16-120) months follow-up, 39 (13%) patients died. Factor analysis revealed 5 factors that explained 54.1% of the original information on the matrix as follows: Factor 1, represented the association between gastrointestinal and renal involvement, male gender and negatively associated with cutaneous features; Factor 2, the association between monogenic relationship with paediatric onset disease; Factor 3, any of musculoskeletal findings with positive constitutional symptoms; Factor 4 any neurologic involvement was associated with ENT and pulmonary findings; Factor 5 cardiac involvement in non-HBV patients (Table). The eigenvalues of the 5 factors were 2.034, 1.470, 1.427, 1.079 and 1.030, in decreasing order, i.e., the highest contribution to the overall variance in the matrix came from the togetherness of the 4 clinical and demographic characteristics that made up Factor 1. Conclusion: Target organ associations could support distinctive subphenotypes in PAN. Factor 1 seems the most severe form. Patients with FMF or DADA2 have distinct target organ associations. The jury is out to decide whether these patients should be classified as 'vasculitis associated with probable etiology' just as HBV-related-PAN. Factor 4 might define a different subphenotype (ANCA- medium vessel vasculitis?). Disclosure of Interests: Omer Karadag: None declared, Ertugrul Cagri Bolek: None declared, Shunsuke Furuta: None declared, Giacomo Emmi: None declared, ALOJZIJA HOCEVAR: None declared, Andrea Hinojosa-Azaola: None declared, Aladdin J Mohammad Speakers bureau: lecture fees from Roche and Elli Lilly Sweden, PI (GiACTA study), Serdal Ugurlu: None declared, Fatma Alibaz-Oner: None declared, Ayten Yazici: None declared, Luca Quartuccio: None declared, Enrica Bozzolo: None declared, Lorenzo Dagna Grant/research support from: Abbvie, BMS, Celgene, Janssen, MSD, Mundipharma Pharmaceuticals, Novartis, Pfizer, Roche, SG, SOBI, Consultant of: Abbvie, Amgen, Biogen, BMS, Celltrion, Novartis, Pfizer, Roche, SG, and SOBI, Giuseppe Alvise Ramirez: None declared, Luca Cantarini: None declared, Gina Gregorini: None declared, Jeannin Guido: None declared, Sara Monti: None declared, Eduardo Martin-Nares: None declared, Franco Schiavon: None declared, Roberto Padoan: None declared, Hajime Kono: None declared, Augusto Vaglio: None declared, Saadettin Kiliçkap: None declared, Ali İhsan Ertenli: None declared, Haner Direskeneli: None declared, Seza Özen Consultant of: Novartis, Pfizer, Speakers bureau: SOBI, Novartis, David Jayne Grant/research support from: ChemoCentryx, GSK, Roche/Genentech, Sanofi-Genzyme, Consultant of: Astra-Zeneca, ChemoCentryx, GSK, InflaRx, Takeda, Insmed, Chugai, Boehringer-Ingelheim